2021
DOI: 10.3390/biology10090830
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive CircRNA Profiling and Selection of Key CircRNAs Reveal the Potential Regulatory Roles of CircRNAs throughout Ovarian Development and Maturation in Cynoglossus semilaevis

Abstract: CircRNAs are novel endogenous non-coding small RNAs involved in the regulation of multiple biological processes. However, little is known regarding circRNAs in ovarian development and maturation of fish. Our study, for the first time, provides the genome-wide overview of the types and relative abundances of circRNAs in tongue sole tissues during three ovarian developmental stages. We detected 6790 circRNAs in the brain, 5712 in the pituitary gland, 4937 in the ovary and 4160 in the liver. Some circRNAs exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Given that most circRNAs are generally produced from pre-mRNA back-splicing [ 24 ], the reason for there being few circRNAs in the W chromosome may be attributed to the fact that the W chromosome of C. semilaevis has the least number of functional genes (317), accounting for 17–34% of other chromosomes [ 9 ]. As in previous studies [ 43 , 57 , 58 , 59 ], the C. semilaevis circRNAs exhibited obvious tissue and sex-specific expression patterns, with gonads showing the largest number of differentially expressed circRNAs in different genders.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Given that most circRNAs are generally produced from pre-mRNA back-splicing [ 24 ], the reason for there being few circRNAs in the W chromosome may be attributed to the fact that the W chromosome of C. semilaevis has the least number of functional genes (317), accounting for 17–34% of other chromosomes [ 9 ]. As in previous studies [ 43 , 57 , 58 , 59 ], the C. semilaevis circRNAs exhibited obvious tissue and sex-specific expression patterns, with gonads showing the largest number of differentially expressed circRNAs in different genders.…”
Section: Discussionsupporting
confidence: 73%
“…In mammals, birds, and teleosts, it was reported that circRNA plays important roles in muscle growth regulation [ 41 , 68 , 69 , 70 ]. Moreover, there are also studies addressing the involvement of circRNAs in the ovary development and sex determination for birds and teleosts [ 43 , 44 , 71 ]. Therefore, the present study not only enriches the potential roles of circRNA in physiological processes, but it also provides new clues for the explanation of fish SSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has revealed that circRNAs display various functions by behaving as gene expression modulators (Jiao et al, 2021), serving as miRNA sponges (Kumar et al, 2017), interacting with proteins (Mo et al, 2021), regulating transcription (Verduci et al, 2021) and translated into proteins (Fontemaggi et al, 2021) ( Figure 1 ). Since exosomes and their biologically active cargoes may offer prognostic information in a range of diseases, as one of their cargo components circRNAs have become a research hotspot in recent years because of their close relation with the development of diseases ( Li et al, 2021 ). These molecules are characterized by a covalently closed loop configuration created through a back-splicing occasion whereby a 3′-5′ phosphodiester bond is formed ( Deng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%